Pharmacological and Non-Pharmacological Strategies for Enhancing Sleep Quality in Athletes - Tymińska, Paulina; Frączek , Julia; Borówka, Karolina; Donocik, Wiktoria; Górka, Piotr; Kawka, Natalia (Quality in Sport, 2025)
Sleep is a critical determinant of recovery, performance, and overall well-being in athletes. Despite its importance, sleep disturbances—including insomnia, delayed sleep onset, and circadian rhythm disruption—are common in athletic populations, driven by both primary factors (e.g., overtraining, evening workouts, jet lag) and secondary factors (e.g., stress, injury, metabolic conditions). These disturbances can impair physical restoration, hormonal balance, and cognitive functioning. This review explores the physiological foundations of sleep in athletes, outlines the multifactorial causes of insomnia, and evaluates pharmacological strategies—including melatonin, non-benzodiazepine hypnotics, cannabidiol (CBD), and certain antidepressants—for managing sleep disorders. While pharmacotherapy may provide short-term benefits in select situations, non-pharmacological approaches such as Cognitive Behavioral Therapy for Insomnia (CBT-I) remain the gold standard due to their long-term efficacy and minimal side effects. An integrated, personalized approach that combines behavioral, physiological, and pharmacological strategies offers the greatest potential for optimizing sleep and supporting sustainable athletic performance.